Enhanced manufacturing quality of thermoplastic composites through infrared-assisted automated fiber placement - Venkatesan, Chadurvedi; Ridhwan, Muhammad; Zulkifli, Faiz; Gupta, Ujjaval; Silva, Arlindo (Frontiers in Manufacturing Technology, 2025)
This study investigates the influence of infrared (IR)-assisted automated fiber placement (AFP) process parameters on the mechanical performance of carbon fiber reinforced thermoplastic composite to fabricate defect-free structures. The effect of process parameters on the processability of carbon fiber-polycarbonate (CF/PC) was analyzed and presented. A structured design of experiments approach was adopted to study the effects of the compaction force and tool temperature on the flexural and lap-shear strength of the manufactured CF/PC parts. The fractography and the interlaminar adhesion were analyzed using digital microscopy. Further, the CF/PC laminated were successfully laid onto a rotating 3D printed polyetherimide cylindrical mold. This work shows, for the first time, the ability of IR-assisted AFP to manufacture CF/PC laminates with improved mechanical properties, demonstrating its potential as a promising material for semi-structural applications.